Safe working in a 7-day service. Experience of hip fracture care as documented by the UK National Hip Fracture Database. (22nd May 2018) - Neuburger, Jenny; Currie, Colin; Wakeman, Robert; Georghiou, Theo; Boulton, Chris; Johansen, Antony; Tsang, Carmen; Wilson, Helen; Cromwell, David A; van der Meulen, Jan
Abstract: Objective: to describe differences in care and 30-day mortality of patients admitted with hip fracture on weekends (Saturday–Sunday) compared to weekdays (Monday–Friday), and their relationship to the organisation of care. Methods: data came from the National Hip Fracture Database (NHFD) linked to ONS mortality data on 52, 599 patients presenting to 162 units in England between 1 January and 31 December 2014. This was combined with information on geriatrician staffing and major trauma centre (MTC) status. 30-day mortality and care were compared for patients admitted at weekends and weekdays; separately for patients treated in units grouped by the mean level of input by geriatricians, weekend geriatrician clinical cover and MTC status. Differences were adjusted for variation in patients' characteristics. Results: there was no evidence of differences in 30-day mortality between patients admitted at weekends compared to weekdays (7.2 vs 7.5%, P = 0.3) before or after adjusting for patient characteristics in either MTCs or general hospitals. The proportion receiving a preoperative geriatrician assessment was lower at weekends (42.8 vs 60.7%, P < 0.001). 30-day mortality was lower in units with higher levels of geriatrician input, but there was no weekend mortality effect associated with lower levels of input or absence of weekend cover. Conclusion: there was no evidence of a weekend mortality effect among patients treated for hip fracture in the English NHS. It appears that clinical teams provide comparably safe and effective care throughout the week. However, greater geriatrician involvement in teams was associated with overall lower mortality.